(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The problem of integration processes in education is considered the most interesting and effective compared to other pedagogical issues. An important factor in implementing integration is identifying methods for establishing connections between elements of wholeness, which should include dialectical categories such as part and whole, content and form, phenomenon and essence, quantity and quality, element and system when forming the curriculum. Within the framework of the informational-content aspect, a comprehensive curriculum should provide conditions for students to develop a scientific-philosophical understanding of the world and form the ability to make worldview generalizations at a high level of thinking activity. Such conditions involve replacing the linear method of creating a comprehensive curriculum with a systematic approach.